Relationship Nutritional Knowledge And Fast Food Consumption Habits With Incidence Of Obsequentness In Adolescents At Sariputra Students, Jambi City - Tania Kanesa (Universitas Widya Gama Mahakam Samarinda, 2023)
Objective: prevalence of overweight among teenagers increasing in Indonesia, namely 9.5% overweight and 4.0% obese, while the prevalence of overweight in the city of Jambi in 2018 is 10.5% overweight and 3.8% obese. The increasing incidence of adolescent obesity caused by level of adolescent nutritional knowledge and the habit of consuming fast food. The aim of this research is to determine the relationship between nutritional knowledge and the habit of consuming fast food with the incidence of obesity in adolescents at Sariputra Middle School, Jambi City. Research Method: This quantitative research with a cross sectional approach. This research was carried out in January-May 2023. Research population was students from Sariputra Middle School, Jambi City with sample size of 68 respondents using random sampling technique. Statistical tests use Chi-Square. Results: The research results showed that 43 (63.2%) had poor knowledge, 35 (51.5%) usually consumed fast food and 37 (54.4%) were obese. The results statistical tests between nutritional knowledge and the incidence of obesity in adolescents show that (p=0.020), and between the habit of consuming fast food and the incidence of obesity in adolescents (p= 0.016). Conclusion: There is relationship between nutritional knowledge and habit of consuming fast food with the incidence obesity in adolescents at Sariputra Middle School, Jambi City. Teenagers should be given education about the factors that cause obesity so teenagers can do physical activity.